Assessment of peripheral neuropathy in type 2 diabetes by diffusion tensor imaging: A case-control study. Issue 145 (December 2021) - Xia, Xinyue; Dai, Lisong; Zhou, Hongmei; Chen, Panpan; Liu, Shuhua; Yang, Wenzhong; Zuo, Zhentao; Xu, Xiangyang
Abstract: Objectives: This study aimed to evaluate diabetes peripheral neuropathy (DPN) by diffusion tensor imaging (DTI) and explore the correlation between DTI parameters and electrophysiological parameters. Methods: We examined tibial nerve (TN) and common peroneal nerve (CPN) of 32 DPN patients and 23 healthy controls using T1-weighted magnetic resonance imaging and DTI. Fractional anisotropy (FA), mean diffusivity (MD), axial diffusivity (AD) and radial diffusivity (RD) of TN and CPN were measured and compared between groups. Spearman correlation coefficient was used to explore the relationship between DTI parameters and electrophysiology parameters in the DPN group. Diagnostic value was assessed by receiver operating characteristic (ROC) analysis. Results: In the DPN group, FA was decreased (p < 0.0001) and MD and RD were increased (p < 0.05, p < 0.001) in the TN and CPN compared with the values of healthy control group. Moreover, in the DPN group, FA was positively correlated with motor nerve conduction velocity (MCV) (p < 0.0001), and both MD and RD were negatively correlated with MCV (p < 0.05, p < 0.001). However, there was no correlation between AD and any electrophysiological parameters. Among all DTI parameters, FA displayed the best diagnostic accuracy, with an area under the ROC curve of 0.882 in TN and 0.917 in CPN. Conclusion: FA and RD demonstrate appreciable diagnostic accuracy. Furthermore, they both have a moderate correlation with MCV.